Pengaruh Persepsi, Pengetahuan Akuntansi Dan Skala Usaha Terhadap Penggunaan Informasi Akuntansi Pada Usaha Mikro Kecil Dan Menengah - Asti Murni Dachi; Mortigor Afrizal Purba (LPPM Universitas Putera Batam, 2023)
This study aims to determine the effect of perception, accounting knowledge and business scale on the use of accounting information on micro, small and medium enterprises. The information gathering strategy is an overview survey of 100 respondents. The method used is a different examination and the type of exploration used in this study is a review technique. the results of the hypothesis test, the perception variable has a significant influence on the use of accounting information with a t count value of 2.422 > t table 1.660, and Sig 0.017 <0.05, accounting knowledge variable obtains a t count value of -0.085 < t table 1.660, and Sig 0.573> 0 .05, so it can be concluded that the accounting knowledge variable does not have a significant effect on the use of accounting information. The business scale variable obtained a t count value of 0.682 <t table 1.660, and Sig 0.497 > 0.05. So it can be concluded that the business scale variable has no significant influence on the use of accounting information. Based on the results of the hypothesis test, the calculated f value is 5.859 > f table 2.699 and Sig 0.001 <0.05. Therefore, it can be inferred that Ho is rejected and Ha is accepted, or, in other words, that the End Match independent variables simultaneously have a significant impact on the dependent variable.